EFEKTIFITAS MEDIA BLOCK DIENES DALAM MENINGKATKAN KONSEP OPERASI PENGURANGAN BAGI SISWA TUNARUNGU - MONIKA LESTARI (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstrack : This researchwas done because the fifth grade deaf students at SDLBN 04 Tarantang Kabupaten Lima Puluh Kota where not eble to subtract by  using the borrowing numbers technique. They were confused because the number to be subtracted was larger than the subtracting numbers. As a result, they placed upside those numbers in the subraction process. This research aimed at proving whether the block dienes media could implove the deaf student’ abilities in subtracting numbers by using the borrowing numbers technique at SDLBN 04 Tarantang. The result of the analyses showed that the students’ abilities in subracting numbers by using the borrowing numbers technique were improved by using the block dienes media. The observation on the baseline condition beforethe intervetion was given (A1) was done seven  times with the changing level of 0%. The observation on the intervention condition (B) was done eight times with the changing level of 70%. Meanwile, on baseline, afterno more intervention was given, the observation was done four times with the changing level of 5%.Keywords       : dienes block media, subtract by  using the borrowing numbers                                 technique, deaf student, mathematic.